Modeling a Born-Digital Factoid Prosopography using the TEI and Linked Data - Daniel L. Schwartz; Nathan P. Gibson; Katayoun Torabi (Journal of the Text Encoding Initiative, 2022)
Although the TEI has traditionally been used for encoding text, its combination of structured and semi-structured data has made it a compelling choice for born-digital, linked-data resources as well. Our intent here is to demonstrate the advantages it offers for digital prosopographies along with a model that can be used for them. Syriac Persons, Events, and Relations (SPEAR) is a born-digital prosopography project in the field of Syriac studies. Where traditional prosopographies focused on prose descriptions of individual persons of significance, SPEAR follows recent developments in research methodologies that instead produce prosopographical factoids. Factoids are structured data about persons drawn from the analysis of historical texts. Most factoid prosopographies use relational databases to model data. Instead, SPEAR uses a customized TEI schema to model factoids that can be queried and visualized in an XML database as well as serialized in HTML for human viewers and in RDF for data sharing. The TEI’s provisions for structured and semi-structured data make it ideal for encoding data from heterogeneous historical source material. Moreover, its linking capabilities connect SPEAR data to related data sets. By modeling prosopographical factoids, and not the source texts themselves, SPEAR offers an example of how a born-digital, data-oriented approach to using the TEI can circumvent some of the challenges posed by the tree structure of XML. It also disrupts traditional understandings of data and stand-off markup through combining linked open data approaches with the use of the TEI.